Longitudinal neuropsychological test performance among HIV seropositive individuals in Uganda - Sacktor, Ned (2013)
OBJECTIVE: To evaluate longitudinal neuropsychological testing performance over a 12 month period among HIV+ individuals, and to evaluate the impact of antiretroviral therapy (ART) initiation on neuropsychological test changes in Uganda. METHODS: The study examined 77 HIV+ individuals recruited from the Infectious Diseases Clinic at Makerere University, Uganda. They underwent detailed sociodemographic, medical history, immune status, functional, neurologic, and neuropsychological evaluations at baseline and 12 months later. Thirty-one individuals initiated ART (ART group) after their baseline visit, whereas 46 individuals were not placed on ART (no-ART group) during those 12 months. Paired samples t-tests were used to evaluate longitudinal changes in neuropsychological test performance for the entire sample, as well as for groups defined by ART initiation and baseline neurocognitive status. RESULTS: The study evaluated 77 HIV individuals (62% women, mean age=37 years, mean education=8 years, mean CD4 count=235 cells/μL). Both the ART and no-ART groups showed significant improvements in tests of verbal memory, executive functioning, motor, and psychomotor speed performance, as well as depression symptoms. The ART group had significant improvements in CD4 count over the 12 months (p<.001) whereas the no-ART group had no CD4 count improvement. CONCLUSION: ART use is associated with improvements in cognitive functioning among HIV+ individuals in Uganda. However, these improvements did not appear to be higher than those seen among HIV+ individuals who did not initiate ART. Possible reasons for this include practice effects among the no-ART group as well as improvements in their mood and overall quality of life.